From 'Kilo-Labor' to CarboGen - Dieter Beer; Thomas Herzig (CHIMIA, 2008)
CarboGen Laboratories AG, a chemical service company focusing on the supply of experimental active pharmaceutical ingredients (API) in kilo quantities to research-based pharmaceutical companies started-up originally in the under-used 'Kilo Lab' of the Institute of Organic Chemistry UZH. The encouragement and help of Prof. Hansen and other organic chemistry professors enabled CarboGen to develop into what is today a company employing more than 300 people with a turn-over of more than 100 million CHF.